Psychometric properties of the Persian version of the relational meaning in life questionnaire in Iranian medical students - Arzpeyma, Mahyar; Kianimoghadam, Amir Sam (Researcher Bulletin of Medical Sciences, 2024)
Background and Objective: Meaning in life is an important parameter in many aspects of human life; and one of the most important aspects of it is relational meaning in life. Relational meaning in life questioner (RMLQ) is the newest instrument that measures this parameter. This study aimed to investigate the psychometric properties of relational meaning in life questioner (RMLQ) in a sample of Iranian medical students. Materials and Methods: In this study, after translating and back‑translating RMLQ, comparisons were made with the original version. The study population consisted of 217 Iranian medical students. Cronbach’s alpha method was used to examine the reliability of the scale and it's score for RMLQ was 0.87. Furthermore, the correlation of the scale was evaluated to determine its criterion validity, using Pearson’s correlation coefficient. Exploratory and confirmatory factor analysis methods were applied for construct validity. Results: Investigation of the psychometric properties of the Iranian version of RMLQ showed its high reliability and confirmatory factor analysis results show the model’s satisfactory fitting. Conclusions: The Persian version of RMLQ is a useful self‑report tool for evaluating the relational meaning in life of Iranian medical students.